Byron's Day in America: The U.S. Squadron and His Lordship's Legacy. Issue 1 (June 2017) - Comet, Noah
Abstract : This essay revisits Byron's 1822 venture aboard the U.S. ships Constitution and Ontario in Livorno, Italy. Drawing from previously unheeded evidence, including a rediscovered painting by William Edward West, I piece together a comprehensive account of the day and consider its significance both to Byron and to the Americans he met. I argue that the visit was of personal and familial consequence for Byron giving voice to the postnational yearnings of his exile. Moreover, for the Americans, the visit caused ripple effects that continued into the 1890s. I went on board the Commodore's ship, Sir! the Constitution or Old Ironsides as she hath been rightly termed: Well! Is that all? Not quite. A short time after I had been on board a man, who wore his hair very long, with full fat cheeks, a healthy lively pair of dark eyes, a cheerful forehead, a man of gentle manners though of a misshapen foot, a man of rank and some note in our small world, came on board. Whom do you guess it was? […] Why nothing but a poet; yet it was a pleasure to have a poet on board an American Squadron, and to have been presented to Lord Byron anywhere else, would not have given me half so much pleasure as it did to meet him on American boards and beneath the American flag. 1 George Bancroft